KUALITASDAN AKTIVITAS ANTIBAKTERI MADU Apis dorsata YANG BERKOLONI PADA TIGA POHON BERBEDA DI KALIMANTAN UTARA - Widowati, Retno; Camin, Yeremiah Rubin; Suryono, Annisa Nur’aini; Azkawati, Elok; Lusiana, Diana Intan Gabriella; Kusmaryeni, Siti; Sinaga, Ernawati (Indonesian Research Gateway, 2018)
Honey has an important role as an anti-oxidant, anti-inflammatory and anti-bacterial agent, make it has high value for therapeutic puposes. North Kalimantan Indonesia is one of the honey producing regions of honey bee Apis dorsata, which colonizing on Gita tree (Alstonia scholaris), Menggeris tree (Koompasia malaccensis), and Pomatodon tree (Canarium decumanum). The aims of this research was to know the quality, phytochemistry and antibacterial activity of three types of honey produced byA. dorsata that colonized on three different trees in North Kalimantan. The honey quality test method was based on SNI 01-3454-2004. The phytochemicals tested included alkaloids, phenolics, hydroquinones, steroids and triterpenoids. Anti-bacterial activity was tested using well diffusion method with honey concentration 25%, 50%, 75% and 100%, against pathogenic bacteriaE.coli, S. typhi, S.aureus, S. epidermidis, and P. aeruginosa. The results showed that the honey tested complied with Indonesian honey quality standard SNI 01-3454-2004, except for water content, acidity and reducing-sugar content. The active compound present in all three types of honey are saponin. Honey from Gita treeat concentration 100% showed the strongest antibacterial activity against all of test bacteria. The antibacterial properties of the honey are probably derived from saponins and low pH of the honey. Honey has an important role as an anti-oxidant, anti-inflammatory and anti-bacterial agent, make it has high value for therapeutic puposes. North Kalimantan Indonesia is one of the honey producing regions of honey bee Apis dorsata, which colonizing on Gita tree (Alstonia scholaris), Menggeris tree (Koompasia malaccensis), and Pomatodon tree (Canarium decumanum). The aims of this research was to know the quality, phytochemistry and antibacterial activity of three types of honey produced byA. dorsata that colonized on three different trees in North Kalimantan. The honey quality test method was based on SNI 01-3454-2004. The phytochemicals tested included alkaloids, phenolics, hydroquinones, steroids and triterpenoids. Anti-bacterial activity was tested using well diffusion method with honey concentration 25%, 50%, 75% and 100%, against pathogenic bacteriaE.coli, S. typhi, S.aureus, S. epidermidis, and P. aeruginosa. The results showed that the honey tested complied with Indonesian honey quality standard SNI 01-3454-2004, except for water content, acidity and reducing-sugar content. The active compound present in all three types of honey are saponin. Honey from Gita treeat concentration 100% showed the strongest antibacterial activity against all of test bacteria. The antibacterial properties of the honey are probably derived from saponins and low pH of the honey. Honey has an important role as an anti-oxidant, anti-inflammatory and anti-bacterial agent, make it has high value for therapeutic puposes. North Kalimantan Indonesia is one of the honey producing regions of honey bee Apis dorsata, which colonizing on Gita tree (Alstonia scholaris), Menggeris tree (Koompasia malaccensis), and Pomatodon tree (Canarium decumanum). The aims of this research was to know the quality, phytochemistry and antibacterial activity of three types of honey produced byA. dorsata that colonized on three different trees in North Kalimantan. The honey quality test method was based on SNI 01-3454-2004. The phytochemicals tested included alkaloids, phenolics, hydroquinones, steroids and triterpenoids. Anti-bacterial activity was tested using well diffusion method with honey concentration 25%, 50%, 75% and 100%, against pathogenic bacteriaE.coli, S. typhi, S.aureus, S. epidermidis, and P. aeruginosa. The results showed that the honey tested complied with Indonesian honey quality standard SNI 01-3454-2004, except for water content, acidity and reducing-sugar content. The active compound present in all three types of honey are saponin. Honey from Gita treeat concentration 100% showed the strongest antibacterial activity against all of test bacteria. The antibacterial properties of the honey are probably derived from saponins and low pH of the honey.